ANSWER
[tex]f(x) - g(x) =2x(2 {x}^{2} + x + 1)[/tex]
EXPLANATION
The given polynomials are;
[tex]f(x) =9{x}^{3} + 2 {x}^{2} - 5x + 4[/tex]
and
[tex]g(x) = 5 {x}^{3} - 7x + 4[/tex]
[tex]f(x) - g(x) =9{x}^{3} + 2 {x}^{2} - 5x + 4 - (5 {x}^{3} - 7x + 4)[/tex]
Expand:
[tex]f(x) - g(x) =9{x}^{3} + 2 {x}^{2} - 5x + 4 - 5 {x}^{3} + 7x - 4[/tex]
Regroup similar terms:
[tex]f(x) - g(x) =9{x}^{3} - 5 {x}^{3}+ 2 {x}^{2} - 5x + 7x + 4- 4[/tex]
Simplify:
[tex]f(x) - g(x) =4{x}^{3}+ 2 {x}^{2} + 2x[/tex]
Factor 2x;
[tex]f(x) - g(x) =2x(2 {x}^{2} + x + 1)[/tex]